The Neurofilament Surveillance Project (NSP): A biomarker study to sample blood quarterly in familial frontotemporal lobar degeneration. (20th December 2022) - Acuna‐Narvaez, Rachel; Heuer, Hilary W.; Forsberg, Leah K.; Alward, Anne; Graham, Danielle; Fishman, Ann; Nelson, Kevin M; Kolander, Tyler; Fillit, Howard M; Galpern, Wendy R; Hung, Serena; Mason, Chris; et al.
Abstract: Background: In familial frontotemporal lobar degeneration (f‐FTLD), plasma levels of neurofilament light (NfL) are elevated at least two years prior to symptom onset and predict future clinical status. The Neurofilament Surveillance Project (NSP), an actively recruiting observational study, seeks to obtain higher resolution data of temporal changes in plasma NfL to better understand its clinical utility in f‐FTLD interventional trials. The NSP is a pre‐competitive collaboration sponsored by the Bluefield Project to Cure FTD and funded by biotechnology and pharmaceutical companies and nonprofit organizations. Method: Participants must be members of families with disease‐causing mutations in C9orf72, MAPT or GRN and enrolled in the ALLFTD natural history study. Up to 335 participants, with roughly equal representation across mutation type, provide plasma quarterly for 3 years (4355 samples total) to enable the observation of peripheral NfL levels longitudinally during disease onset and progression. Plasma is collected by certified mobile research nurses during remote visits, and NfL is measured in batch at least every 6 months. NfL measurements from one plasma aliquot per draw will be correlated with annual assessments obtained in the ALLFTD study, including measures of disease severity (CDRÒ+NACC‐FTLD, CGI, etc.), cognitive function from the UDS Neuropsychology Battery, and volumetric MRI data. Additional plasma aliquots are reserved for future analyses of other biomarkers during the course of the study; another subset of aliquots is reserved to share with interested investigators after the study ends. Result: As of 1/19/22, the NSP had enrolled 161 participants, including 62 from C9orf72 kindreds, 60 from MAPT kindreds, and 28 from GRN kindreds. One‐hundred forty‐five participants had completed their initial visit, and 109 had completed more than 3, and up to 5, quarterly blood draws. Enrollment and study visits are ongoing despite COVID‐related limitations. Conclusion: The quarterly blood sampling from this study, combined with annual comprehensive clinical assessments through the ALLFTD natural history study, will enable a more detailed understanding of when and how NfL levels change during phenoconversion and/or disease progression in f‐FTLD mutation carriers. These data will be especially informative in the context of the targeted investigational therapeutics for f‐FTLD now entering clinical trials.